Efektivitas Kombinasi Tablet Fe dan Konsumsi Kurma terhadap Peningkatan Kadar Hemoglobin pada Remaja Putri - Ayuk Naimah; Lailaturohmah (Poltekkes Kemenkes Kupang, 2026)
Background: Anemia among adolescent girls remains a major public health problem that contributes to reduced immunity, fatigue, and impaired cognitive performance. This condition is commonly associated with inadequate iron intake and suboptimal iron absorption. Objectives: This study aimed to analyze the effect of iron (Fe) tablets combined with date consumption on hemoglobin levels among adolescent girls at SMK Puspa Bangsa Banyuwangi in 2025. Methods: A quasi-experimental design with a pretest-posttest control group was applied. The study involved 30 respondents divided into an intervention group (Fe tablets and dates) and a control group (Fe tablets only), with 15 participants in each group. Hemoglobin levels were measured before and after the intervention and analyzed using paired and independent t-tests. Results: The results indicated an increase in hemoglobin levels in both groups; however, the intervention group showed a significantly greater improvement (p < 0.05). Conclusions: The combination of Fe tablets and date consumption is more effective in improving hemoglobin levels compared to Fe tablets alone.